Organizational commitment and its impact towards job performance among BERNAS' employees / Muhammad Adri Abd Rahman - Abd Rahman, Muhammad Adri (Faculty of Business and Management, 2014)
Job Performance is a serious issue in every organization not only in BERNAS or other random organization in Malaysia but in any organization in the whole world to be precise. Previous study have shown that, job performance of an individual plays vital role in an organization's growth because it highly influences the overall firm's performance and also functions as the key variable in work and organizational psychology It is due to the fact, since by having committed employees, organization can achieve a great performance as a whole. However, past study have been conducted that there were varieties of components that impact on employees' job performance but according to Allen (1990), employees‟ organizational commitment has serious and potential effects on organization’s performance and can be an important predictor of organizational effectiveness. Therefore, this study was conducted to determine organizational commitment and its impact towards job performance among BERNAS' employees. Participants were 151 BERNAS' employees who completed the 9-item by Tawiah (2009) for Job Performance and 24-item by Allen & Meyer (1990) for Organizational Commitment includes 8-item for Affective Commitment, 8-item for Continuance Commitment and 8-item for Normative Commitment. All the data and information gathered were coded, process and analyzed by using Statistical Package for Social Science (SPSS) version 20 to produce a relevant and accurate result. The result of the findings will help employees to gain awareness on the main factor and help them to manage and improvise their job performance in the near future. Recommendations for future research also have been discussed.